2011
DOI: 10.4161/epi.6.5.15221
|View full text |Cite
|
Sign up to set email alerts
|

RNA templating the epigenome

Abstract: C ellular pathways must be synergized, -controlled and organized to manage homeostasis. To achieve high selectivity within the crowded cellular milieu the cell utilizes scaffolding complexes whose role is to bring molecules in proximity thereby controlling and enhancing intermolecular interactions and signaling events. To date, scaffolds have been shown to be composed of proteinaceous units; however, recent evidence has supported the idea that non-coding RNAs may also play a similar role. In this Pointof-View … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(73 citation statements)
references
References 63 publications
1
71
0
1
Order By: Relevance
“…One possibility is that Bmi1 acts as a limiting factor that can grossly raise or lower the overall activity of PRC1, while additional factors are responsible for the graded activity of the complex over the rostrocaudal axis. One candidate for such a partner is a long noncoding RNA (lncRNA), which appears to regulate PRC binding at several loci, including Hox clusters (Spitale et al 2011). Differential transcription of such an RNA over the rostrocaudal axis could have the effect of grading PRC recruitment to Hox loci.…”
Section: Prc1 Activity Levels Control Hox Expression In Mnsmentioning
confidence: 99%
“…One possibility is that Bmi1 acts as a limiting factor that can grossly raise or lower the overall activity of PRC1, while additional factors are responsible for the graded activity of the complex over the rostrocaudal axis. One candidate for such a partner is a long noncoding RNA (lncRNA), which appears to regulate PRC binding at several loci, including Hox clusters (Spitale et al 2011). Differential transcription of such an RNA over the rostrocaudal axis could have the effect of grading PRC recruitment to Hox loci.…”
Section: Prc1 Activity Levels Control Hox Expression In Mnsmentioning
confidence: 99%
“…They could regulate gene expression and function, including dosage compensation [15,16], genome rearrangement [17], chromatin modifications [7,18,19], gene imprinting [20,21,22], alternative splicing [23], nuclear-cytoplasmic trafficking [24,25,26], cell cycle control [27,28,29] and inactivation of major tumor suppressor genes [30,31]. Wang et al [32] summarized the functions of lncRNAs as signals [33], decoys [34,35], guides [15] and scaffolds [18,36].…”
mentioning
confidence: 99%
“…Moreover, recent studies have indicated that lncRNAs participated in a wide range of biological pathways and cellular processes. They could regulate gene expression and function, including dosage compensation [15,16] [18,36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNA genes exhibit tissue‐specific expression patterns and regulate expression of the genes that are pivotal to development and cancer (Cabili et al ., 2011; Guttman et al ., 2009). lncRNA can act as a recruiter and scaffold for assembly of chromatin modifiers on their target genes (Chu et al ., 2011; Gupta et al ., 2010; Spitale et al ., 2011; Tsai et al ., 2010; Wang and Chang, 2011). The lncRNA HOX transcript antisense RNA (HOTAIR) is elevated in breast cancer and promotes metastasis (Gupta et al ., 2010; Rinn et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%